Conflicting objectives in democracy promotion: avoiding blueprint traps and incomplete democratic transitions - Julia Leininger; Sebastian Ziaja (Deutsches Institut für Entwicklungspolitik (DIE), 2014)
Western donors attempting to promote democracy across the globe face a dilemma. Democracy is a highly valued policy goal, but they are fearful that the path to democ¬racy will undermine another highly valued goal – political stability – and potentially cause widespread violence in the recipient countries or beyond. We ask whether these fears have empirical support and how donors can balance the potentially conflicting objectives of democratisation and stability when intervening in governance matters. Recent research at the German Development Institute shows that fears about the destabilising effects of democratisation do indeed have some empirical support (Leininger et al 2012; Ziaja 2013). But these fears deflect attention from the bigger problem of “getting stuck in the middle”. Hybrid regimes that exhibit authoritarian traits under a façade of formal democratic institutions constitute, in the long run, a larger security risk than attempts to make these countries more democratic. Hybrid regimes also hamper economic development, thus constituting an additional, indirect, risk of violent conflict. The promotion of democracy is hence a laudable effort, but it may itself carry risks. A recent DIE study of 47 African countries suggests that support for democracy increases popular mobilisation in the short run, leading to increased demonstrations and riots. However, the same study produced no evidence that democracy support is likely to spark civil wars. Increased mobilisation is thus rather a sign of aid effectiveness than a reason to worry. Yet, to be effective in the long run and to help steer popular demands into peaceful channels, democracy support must assist domestic actors in building institutions that fit the needs of their society. In the past, the potentially de¬stabilising consequences of popular participation have seduced would-be engineers of social change into re¬stricting competition in young democracies. This is a bad idea, as our recent research shows: narrow, elite pacts have, on average, led to worse political outcomes than open competition. The best contribution that donors can make from the out¬side is to enable marginalised groups to participate in crea¬ting the institutional setup. This is best achieved when many donors promote democracy simultaneously. Only then can they avoid the “blueprint trap”, which snaps shut when donors try to impose – advertently or inadvertently – an institutional setup on the partner country that does not fit its society's needs. Diversity on the donor side increases the chances of finding a context-adequate institutional design. These findings suggest that an overly cautious sequencing approach to democracy promotion – stability first, only then democracy – has little empirical support. Most countries in the world embarked on a (formally) democratic path more than two decades ago. A gradualist approach that builds institutions while at the same time encouraging mobilisation is thus the more viable approach. Recommendations in brief: Promote democracy now Keep democracy aid diverse Encourage endogenous, inclusive polity design Enforce conditionality on conflict resolution mechanisms in institutional design Balance trade-offs of democratic transitions.
Keywords: 330; Demokratie und Autokratie; Sicherheit; Frieden und fragile Staaten